Ketupat dan identitas budaya jawa: Makna, tradisi dan nilai sosialnya - Kamila, Ila Nur; Hasaniyah, Nur (Maliki Interdisciplinary Journal, 2025)
Ketupat is a culinary icon that not only has gastronomic value, but also has deep symbolic meaning in Javanese culture, especially in the Eid al-Fitr celebration. This article aims to examine the meaning of ketupat in the context of Javanese cultural identity, as well as the traditions and social values contained therein. Ketupat, made from rice and wrapped in coconut leaves, is not just a dish, but also a symbol of purity, togetherness and social harmony. In Javanese tradition, ketupat is an inseparable part of religious ceremonies and social rituals that strengthen bonds between individuals in the community. This article explores how ketupat plays a role in maintaining deep local cultural values, as well as its relevance in the lives of contemporary Javanese society.